Faktor-faktor yang Mempengaruhi Sikap Perawat dalam Keselamatan Pasien: Systematic Review: Factors Influencing Nurse Attitudes in Patient Safety: Systematic Review - Annisa Rahmi Galleryzki; Rr. Tutik Sri Haryati; Dadan Bardah; Kartika Mawar Sari Sugianto; Endang Sudjiati; Elisabet Herlyani Bota Koten (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2023)
Nurses have a critical role in ensuring care delivery focuses on patient safety and injury prevention during treatment. Positive attitudes toward injury prevention can improve patient safety; however, several factors such as age and work experience are believed to have influenced nurses’ safety attitudes. A systematic review searched data through online databases such as Scopus, ScienceDirect, Wiley Online Library, and EBSCO for articles published between 2010 and 2020. The keywords used were